If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 5q = 33 Solving 4p + 5q = 33 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5q' to each side of the equation. 4p + 5q + -5q = 33 + -5q Combine like terms: 5q + -5q = 0 4p + 0 = 33 + -5q 4p = 33 + -5q Divide each side by '4'. p = 8.25 + -1.25q Simplifying p = 8.25 + -1.25q
| 4a-2a/5=18 | | 18x1/3 | | 3x^2-3x-4x-6=0 | | 3D+D+4d-8d= | | y*1/8=128 | | 21/3x18 | | 5y+8=2y-10 | | 24/x-3=3 | | (7x+7)5y=140 | | 7x+10=3x-22 | | 7x+7(5y)=140 | | 12-6(2x-3)= | | 2(3s+9)=63 | | 3(3s+5)=60 | | 3(4x-2)=x+16 | | 4x-35=3(5x+3) | | 4log(2x-1)=0 | | (u-5)*8=16 | | 4(2l+5)=100 | | 4(3s+7)=172 | | 6(l+6)=168 | | (e+2)*6=42 | | C=60t+800 | | (f/6)-4=1 | | (q-3)*6=12 | | 150/144 | | (2x+1)/4=2 | | 21=63 | | sin(21)=cos(5x+9) | | 2a+8b-2a+b= | | y=200x+150 | | 5(3x-1)=1 |